Proposed upgrading to the existing interior design of P. Ramlee Memorial Gallery at No 22, Jalan Dedap, Taman P.Ramlee, 53000, Setapak, Kuala Lumpur for National Archives of Malaysian / Nur Izzati Mohd Bakry - Mohd Bakry, Nur Izzati (Faculty of Architecture, Planning and Surveying, 2012)
The purposes of this project are to upgrade and provide a better accommodation space for the existing P. Ramlee Memorial Gallery at No 22, Jalan Dedap, Taman P. Ramlee 53000, Setapak, Kuala Lumpur. This project will propose new design element in the memorial in order to enhance the visitor who to the memorial and get some information about the life of P. Ramlee. The existing memorial hasn’t been upgrade since 2002. The gallery still used old design display and lack of new technologies approach. The aim of this project is to upgrade the gallery to be more attractive by providing a better circulation new technologies display item and good lighting. The project methodologies that have been carried out by interview and observation will be done in order to get primary data. For secondary data, books, and internet will be used. The case studies for references in this project are done at Tunku Abdul Rahman and Tun Hussien Onn and two from international case study.